2008
DOI: 10.1016/j.marchem.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the reactive iron pool by marine diatoms

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. Abstract Short term (2 days) laboratory experiments were performed to study the change in irradiance induced production of Fe(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 84 publications
(129 reference statements)
5
31
0
Order By: Relevance
“…In the UVSW without exudates the Fe(II) concentration continued decreasing exponentially reaching the detection limit after 20 min, whereas in UVSW with added diatom exudates the Fe(II) concentration remained at about 30 nmol L −1 decreasing only very slightly with time. The photochemical effect of the exudates was therefore strong enough to result in a net stabilising effect on Fe(II) after 7 min, confirming results reported by Rijkenberg et al (Rijkenberg et al, 2008) who observed irradiance dependent photoreduction of Fe(III) in the presence of the diatom Thalassiosira "sp". Total iron concentrations from the beginning and end of this experiment did not change, indicating no major loss of Fe from the system.…”
Section: Experiments 3: Effect Of Diatom Exudates and Uva/b Radiation supporting
confidence: 87%
“…In the UVSW without exudates the Fe(II) concentration continued decreasing exponentially reaching the detection limit after 20 min, whereas in UVSW with added diatom exudates the Fe(II) concentration remained at about 30 nmol L −1 decreasing only very slightly with time. The photochemical effect of the exudates was therefore strong enough to result in a net stabilising effect on Fe(II) after 7 min, confirming results reported by Rijkenberg et al (Rijkenberg et al, 2008) who observed irradiance dependent photoreduction of Fe(III) in the presence of the diatom Thalassiosira "sp". Total iron concentrations from the beginning and end of this experiment did not change, indicating no major loss of Fe from the system.…”
Section: Experiments 3: Effect Of Diatom Exudates and Uva/b Radiation supporting
confidence: 87%
“…Also Boye et al (2003) found relatively low K 0 values in surface waters at 411N (10 20.6 -10 21 ). This indicated that the ligands presumably coming from the phytoplankton are relatively weak, supporting the conclusion of Rijkenberg et al (2008b) that phytoplankton can modify ligand characteristics. Others stated that ligands related to phytoplankton activity belong to the relatively strong ligand group (Rue and Bruland, 1997;Cullen et al, 2006;Hunter and Boyd, 2007).…”
Section: Fe-binding Ligandssupporting
confidence: 70%
“…The beneficial effects of the non-lytic Alexandrium supernatant on Chaetoceros spp. may be explained by metal complexing properties of extracellular organic material, derived from phytoplankton, which can affect trace metal availability as well as seawater toxicity (Croot et al, 2000;Vasconcelos et al, 2002;Rijkenberg et al, 2008). In a laboratory study, growth of the diatom Phaeodactylum tricornutum was enhanced by algal exudates of different macro-and microalgae.…”
Section: Discussionmentioning
confidence: 99%